alfa-MSH signalling via melanocortin 5 receptor promotes lipolysis and impairs re-esterification in adipocytes - Rodrigues, Adriana (2013)
The melanocortin system has a clear effect on the mobilisation of stored lipids in adipocytes. The aim of the current study was to investigate the role of melanocortin 5 receptor (MC5R) on alpha-melanocyte-stimulating hormone (alpha-MSH)-induced lipolysis in 3T3-L1 adipocytes. To this end, MC5R expression was decreased by small interfering RNA (siRNA), which significantly impaired the alpha-MSH stimulation of lipolysis, as determined by glycerol and nonesterified fatty-acid (NEFA) quantification. The functional role of alpha-MSH/MC5R on triglyceride (TG) hydrolysis was mediated by hormone-sensitive lipase (HSL), adipose triglyceride lipase (ATGL), perilipin 1 (PLIN1) and acetyl-CoA carboxylase (ACC). Immunofluorescence microscopy revealed that phosphorylated HSL clearly surrounded lipid droplets in alpha-MSH-stimulated adipocytes, whereas PLIN1 left the immediate periphery of lipids. These observations were lost when the expression of MC5R was suppressed. In 3T3-L1 adipocytes, alpha-MSH-activated MC5R signals through the cAMP/PKA and MAPK/ERK1/2 pathways. PICA was fundamental for HSL and PLIN1 activation and lipolysis regulation. ERK1/2 inhibition strongly interfered with the release of NEFAs but not glycerol. In addition, the intracellular TG levels, which were decreased after MC5R activation, were restored after ERK1/2 inhibition, indicating that these kinases are involved in NEFA re-esterification rather than lipolysis regulation. This notion is also supported by the observation that the alpha-MSH-mediated activation of phosphoenolpyruvate carboxykinase (PEPCK) was abolished in the presence of ERK1/2 inhibitors. Altogether, these results indicate that alpha-MSH-activated MC5R regulates two tightly coupled pathways in adipocytes: lipolysis and re-esterification. The global effect is a decrease in adipocyte fat mass, which is important for strategies to ameliorate obesity.